Transferência léxico-semântica no multilinguismo - Fonseca, Laís Cirne Avila da (2014)
Multilingualism as a social and linguistic phenomenon is still not much explored in Brazil. Even though the issue has gained much attention in the country, the international literature in the area is wider. One of the investigated issues is the crosslinguistic transfer on different levels (phonological, morphosyntactic, semantic and discourse-pragmatic) between the individual s known and used languages. The focus of the present study is to analyze the transfer on the lexical-semantic level between the previous languages learned (Portuguese as L1 and English as L2) to the written production of French as L3. More specifically, this study aims at analyzing: (1) the category of the lexical-semantic transfer, whether formal or semantic, more present in the participants written production; (2) the direction in which more lexical-semantic transfer occur, if L1-L3 or L2-L3. Two hypotheses were formulated: (1) it is assumed that, according to Ecke (2001), there will be more formal lexical transfer, which happens when the learner notices a structural similarity between L1 or L2 and the intended word in the L3 and (2) it is assumed that the transfer should more frequently happen from L2 to L3 due to the status of foreign language as in Llama, Cardoso and Collins (2007), Shooshtari (2009), Bardel and Falk (2007). Twelve (12) young adults participated in the present study, all native speakers of Portuguese (L1), English speakers as L2 with an intermediate proficiency level and French learners as L3 with a basic proficiency level. The results show that the majority of the transfer was lexical of the form typology. The source of the transfer was, in the majority of the cases, the L1. It was concluded that typological proximity can be one of the main reasons for the recurrence to the L1 in the L3 written production.